ANALISIS TELUR CACING SOIL TRANSMITTED HELMINTH (STH) PADA PETANI SAYUR DI KARTAMA PEKANBARU - Berliana N.R.S. Aritonang (Akademi Kesehatan John Paul II Pekanbaru, 2020)
Worm infection caused by the Soil Transmitted Helminth (STH) are one of health problem in indonesia, as in vegetable farmers. Worm that are transmitted through the Soil are Ascaris lumbricoides, Trichuris trichiura, and Hookworms (Necator americanus and Ancylostoma duodenale). The purpose of this study was to determine the presence or absence of Soil Transmitted Helminth (STH) egs in vegetable farmer of Kartama Pekanbaru. This study used a cross-sectional design with the sedimentation method. Microscopic observation of 27 sample showed that STH eggs were not found in both faeces and nails samples. The examination method used was sedimentation method the population in this study were farmers in Kartama Pekanbaru who did hot use gloves or footwear during gardering.